Research on body image cognition, social support and illness perception in breast cancer patients with different surgical methods - Liu, Yuhan; Liu, Wanli; Ma, Yinglu; Yang, Xiaoyue; Zhou, Han; Zhang, Tingting; Shao, Shuhong (Frontiers in Psychology, 2022)
In parallel with the rapid rise in breast cancer incidence, there is also a noticeable rise in the number of patients who experience persistent negative body image cognition after breast cancer surgery. This study aimed to explore the differences in illness perception, social support, and body image cognition among breast cancer patients with different surgical methods, and the correlation, regression, and mediation among the three variables. The Brief Illness Perception Questionnaire (BIPQ), the Social Support Rating Scale (SSRS) and the Body Image Cognition after Breast Cancer Questionnaire (BIBCQ) were used to evaluate breast cancer patients’ illness perception, social support and body image cognition. Data analyses were performed by descriptive statistics, independent samples t-test, analysis of variance (ANOVA), Pearson correlation, and linear regression. The mediation was explored by the PROCESS V3.3. The study found that breast cancer patients undergoing radical mastectomy (RM) and modified radical mastectomy (MRM) demonstrated more negative illness perception, body image cognition, and lower social support compared with the patients receiving nipple-sparing mastectomy (NSM; p < 0.05). The subscale cognitive representation (CR) of BIPQ was strongly positively correlated with BIBCQ (p < 0.05). Illness perception positively predicted body image cognition (p < 0.01), while social support negatively predicted body image cognition. Social support partially mediated illness perception and body image cognition, exhibiting a positive role in post-operative body image cognition.